A concorrência por lugares entre as mídias jornalísticas impressas: estudo das estratégias de produção de sentidos no discurso autorreferencial - Ribeiro, Daiane Bertasso (2010)
This work is part of the current scenario of media coverage in the range of access to new information technologies and communication as well as the many media devices, affects different social systems and even the media themselves, changing ways of doing and relationship between the contacts and the degree of complexity of these processes and relationships. In this context, we recognize the places crowded by the media of print journalism Santa Maria - RS, by studying the strategies of production of meaning in self-referential discourse of newspapers A Razão and Diário de Santa Maria, in the campaign for municipal elections 2008. We seek to investigate what role that self-referential journalism of print media of Santa Maria seeks to establish through their discourses? From this, our specific objectives are: Contextualizing the impact of self-referentiality as a result of the change strategies of media devices as a result of mediatization; Present method of construction of selfreferential journalistic discourse the media, linking theoretical and empirical knowledge; Identify the core meanings/discursive formations and the scene of enunciation of self-referential discourses that will enable us to visualize the image of himself (discursive ethos) constructed by each newspaper; Recognize the communication contract proposed by the self-referential discourses of the newspapers in study. We used as theoretical and methodological Discourse Analysis of the French line, especially developed by Dominique Maingueneau (1997, 2006, 2008). Thus, the analysis of the discursive strategies of self-referentiality newspaper A Razão and Diário de Santa Maria helped us to verify that newspapers compete to fill posts of legitimate statements of facts or information to the public space in mediated society. This competition for places in the context of media coverage changes the processes and journalistic practices, and modes of enunciation of his discourses. Thus, the journalistic system becomes a space actorization of events and information that become news, showing its reality, how to stage makes the process of newsworthiness. Thus, it appears that apart from the competition between the media system is the journalistic competition to the place that speaks of legitimate society also mediated with the other social systems. Therefore, this study points to the need for future research should discuss and reflect the power relations of the journalistic system with other systems and points to the need to rethink this logic self-referential change the current system to a journalistic role agent democratic in contemporary public space.